Revitalisation of organic and peat soils - Tang, Bee Lin (2011)
Ground improvement projects are often necessary and site – specific to ensure project success. The author hypothesizes that problematic soil, which are often mass replaced can be revitalised with modest proportions (<10%) of Ordinary Portland Cement as a binder to make a positive contribution to economic, green engineering, and resource sustainability. Deep cement mixing (DCM) techniques have proved to be successful worldwide and use large proportions (circa 200%) of cement, lime and/or fly ash in dry or wet mixing to form in-situ piles with enhanced strength and stiffness in comparatively short time. Revitalisation of organic and peat soils is not a practice currently adopted in Malaysia which has a distribution of over 1.5 million ha of such challenging soils. Such soils have high water and organic content and their mechanical chemical and biological properties degenerate with time. Land shortage for development promotes land reclamation. The shear strength and stiffness behaviour of these heavily organic soils and the revitalised soils is central to this research study. Peat soil from Pontian, Johor and an organic soil from Bukit Rambai, Malacca are investigated with laboratory controlled cement slurry mixing at water cement ratios of 3.5,7,14,140 for peat and 5,10,15 for organic soil. Specimens of these soil mixtures were prepared in polyvinyl chloride tubes (50 mm diameter 300 mm long) and cured at room temperature of 25o C and relative humidity of 50% for 7,14 and 28 days. Unconfined compressive strength, consolidated undrained triaxial, bender element, and one dimensional consolidation tests were done to assess the strength and stiffness improvements of the ‘revitalised soils’. Increases of up to 30% and 16% in unconfined compressive strength and 229% and 0.9% in Go for Pontian Peat and Malacca organic soil respectively are reported in this study. Keywords: cement slurry, organic soils, peat soils, revitalisation, strength, stiffness